2012
DOI: 10.1080/1059924x.2012.658009
|View full text |Cite
|
Sign up to set email alerts
|

Children's Environmental Health in Agricultural Settings

Abstract: Children residing in rural settings may encounter environmental hazards derived from agricultural production activities. Health consequences of organic dusts, farm chemicals including pesticides, machinery noise, excess sun exposure, and zoonotic infectious agents have been clearly described among farm-working adults. The author reviews the related evidence base on child health with a life-stage perspective on their differential exposure and vulnerabilities. Methemoglobinemia among infants consuming nitrate-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 86 publications
1
10
0
1
Order By: Relevance
“…These findings corroborate previous studies which reported lesser use of sun protection by young people (below age 30) (20,28). Young workers might also do more physical outdoor tasks and less administrative or in-vehicle work than more senior workers (29,30). However the pro-tanning attitude was not found to be significantly associated with age (p = 0.58).…”
Section: Discussionsupporting
confidence: 89%
“…These findings corroborate previous studies which reported lesser use of sun protection by young people (below age 30) (20,28). Young workers might also do more physical outdoor tasks and less administrative or in-vehicle work than more senior workers (29,30). However the pro-tanning attitude was not found to be significantly associated with age (p = 0.58).…”
Section: Discussionsupporting
confidence: 89%
“…Agricultural communities may have fewer urban ambient air pollution sources (e.g., motor vehicle traffic and industrial emissions), but have substantially more unique local sources like pollen and similar aeroallergens, and emissions from industrial-scale agricultural operations including windblown dust, animal agricultural emissions and pesticide drift from large crop-growing operations, 12,13 all of which have been suggested to contribute to respiratory disease. 14,15…”
Section: Introductionmentioning
confidence: 99%
“…As crianças que vivem em ambientes rurais encontram riscos ambientais derivados de atividades de produção agrícola, tanto pela exposição múltipla e contínua quanto pelas condições de trabalho e saúde, que podem agravar consideravelmente os efeitos produzidos por esses contaminantes químicos (Perry, 2003;Karr, 2012;Miller, Marty e Landrigan, 2016).…”
Section: Introductionunclassified